P701 New onset spondyloarthropathy in vedolizumab treated IBD patients. (15th January 2020) - Tetley, A M; Lobaton, T; Truyens, M; Katsanos, K H; de Boer, K H N; Pattinson, A; Molnar, T; Filip, R; Michalopoulos, G; Sebastian, S
Abstract: Background: Patients with IBD may have associated spondyloarthropathy. Vedolizumab is used for IBD with its actions considered to be gut specific but the impact of this treatment on existing arthritis or development of arthritis is uncertain. Integrins and adhesion molecules play a role in the interception of recirculating activated lymphocytes between the gut and the synovial membrane due to the inhibition of the alpha4beta7 integrin homing at the level of the gut. We aimed to describe characteristics and outcomes of spondyloarthropathy in IBD patients treated with vedolizumab. Methods: We retrospectively collected data on a multicentre cohort of IBD patients with arthropathy which developed following use of Vedolizumab for IBD. This was a part of the European Crohn`s and Colitis Organisation (ECCO) initiated CONFER (Collaborative Network for Exceptionally Rare case reports) project. Data were recorded on a standardised case report form and analysed with descriptive statistics. Results: We report data on 14 cases of new onset spondyloarthropathy and 1 case of worsening of pre-existing arthropathy from 7 contributing centres. Vedolizumab was used for 6 patients with CD and 8 patients with UC. IBD was in remission in all but 3 patients at the time of development of the joint features. Sacroiliitis was the manifestation in 10 patients, 3 of whom had both sacroiliitis and peripheral arthritis. Three patients had peripheral arthritis alone and one patient had peripheral arthritis with enthesitis. One patient had worsening of peripheral arthropathy following use of vedolizumab. Raised inflammatory markers (CRP, ESR or both) were recorded only in one-third of the patients. MRI was abnormal in 9 patients being the marrow oedema in SI joints the commonest feature. One patient had abnormal bone scintigraphy and in another patient plain X-ray and ultrasound was used in confirming diagnosis. Eight of the patients developed arthropathy within days after a single infusion of vedolizumab. five patients needed hospitalisation for treatment The treatments used included systemic steroids (11 patients), Intraarticular steroids (3) NSAID (2 patients), Cox inhibitor (1), methotrexate (2) Hydroxychloroquine (1). Vedolizumab was discontinued in 11 of the patients. In the majority of patients (11/15) it took many months to resolve the arthropathy. On re-challenge with vedolizumab, the arthropathy recurred in 2 out of the 3 patients. Conclusion: This case series demonstrates the potential risk for development of spondyloarthropathy with vedlizumab in IBD patients which is unrelated to the activity of IBD and can have significant impact including need for use for systemic steroids and hospitalisation. Larger prospective cohorts are needed to confirm these results.